Pengaruh Kompetensi Pengembangan Sumber Daya Manusia dan Budaya Organisasi Terhadap Kinerja Pegawai Pada BPJS Ketenagakerjaan Kanwil Sulawesi Maluku - Asmar, A.; Razak, St. Rahmi (Doktor Ilmu Manajemen, Universitas Muslim Indonesia, 2023)
This study was conducted to analyze the test effect of competence to employee performance at BPJS Employment Office of Sulawesi, Maluku, to analyze the effect of human resource development to employee performance at BPJS Ketenagakerjaan Office of Sulawesi, Maluku, to analyze the influence of organizational culture influence on employee performance BPJS Ketenagakerjaan Regional Office Sulawesi, Maluku, to analyze the more dominant variables affect the performance of employees at the Regional Office of the BPJS Ketenagakerjaan Sulawesi, Maluku. This study uses data questionnaire, literature study and interviews with quality test data analysis techniques, classic assumption test, multiple linear regression analysis and hypothesis testing. The study found that the results of the regression equation obtained results for the regression coefficient for the competence of 0.343 and has a value ρvalue of 0.002, so it can be concluded that the competency has a positive influence and significant impact on employee performance BPJS Ketenagakerjaan Office of Sulawesi, Maluku, the results of the regression equation to variable human resource development at .290, and has a value ρvalue amounted to 0,018, so that it can be concluded that the development of human resources has a positive influence and significant impact on employee performance BPJS Ketenagakerjaan Office of Sulawesi, Maluku, based on the results of data processed regression coefficient of the obtained regression coefficients for the variables Organizational culture of 0.724 and has value ρvalue = 0,000 so it can be concluded that organizational culture has a positive and significant influence terahdap employee performance on BPJS Ketenagakerjaan Office of Sulawesi Maluku, from h Regression test regression then it can be concluded that the organizational culture variable is the dominant variable affecting the improvement of employee performance on BPJS.